Predictive Capabilities and Limitations of Stream Interaction Region Observations at Different Solar Longitudes - R. C. Allen; G. C. Ho; L. K. Jian; G. M. Mason; S. K. Vines; D. Lario (Space Weather)
Abstract Advanced warning of a stream interaction region (SIR) or corotating interaction region (CIR) impinging upon the magnetosphere of Earth is important for space weather forecasting, due to the ability of SIRs/CIRs to trigger geomagnetic storms and affect ionospheric composition and winds. However, a focused investigation of the likelihood that either an L5 monitor or Earth‐trailing “string‐of‐pearl” constellation of satellites would be able to serve as an effective warning buoy for SIRs/CIRs that will affect the near‐Earth space environment has yet to be extensively performed. Through comparing 10 years of SIRs/CIRs observed at L1 and at STEREO, we have investigated the probability of sequentially detecting SIRs/CIRs at two locations as a function of the difference in heliospheric longitude and latitudinal separation between the two spacecraft. By examining the probability of repeat detection of SIRs/CIRs using variable separation distances between two observing points, we explore the utility of an Earth‐trailing monitor for SIR/CIR predictability (i.e., 74.6% of SIRs observed at L5 reach L1 within ±3 days of rigid corotation). While the probability of predicting the occurrence of SIRs/CIRs at another spacecraft decreases with longitudinal separation, there is no significant dependence on latitude. The primary source of error in reliably predicting the arrival time of an SIR/CIR is uncertainty in the rotational speed of the structure. While an L5 monitor would be an advancement in our operational warning ability, an Earth‐trailing “string‐of‐pearls” constellation utilizing multiple point of measurements would engender much more certainty in predicting the arrival time of SIRs/CIRs.